1981
DOI: 10.1021/ac00227a030
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of iron(II) and iron(III) at micromolar concentrations by differential pulse polarography

Abstract: normalized Ai, is 75% maximum) and minimum peak width (W,p is 124/n mV compared to its minimum value of 90/n mV). A value of IAEl = 50/n mV (at T = 25 "C) is thus recommended for analytical purposes. Of course in the solution of analytical problems where n may not be known, or where a multicomponent mixture of species with different n values or similar values of Ellz is present, the pulse height should be optimized experimentally.Analytical figures of merit such as detection limits have not been determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…A differential pulse polarographic method for Fe(II) and Fe(III) determination at mM concentration ranges was also developed; it took advantage of nonaqueous solvents both for the extraction and electrochemical determination of the analyte(s) [24]. In spite of its redox speciation ability and interesting sensitivity, because of the complexity of the procedures this method does not seem particularly suitable for quick analysis and for``in ®eld'' determinations.…”
Section: Introductionmentioning
confidence: 99%
“…A differential pulse polarographic method for Fe(II) and Fe(III) determination at mM concentration ranges was also developed; it took advantage of nonaqueous solvents both for the extraction and electrochemical determination of the analyte(s) [24]. In spite of its redox speciation ability and interesting sensitivity, because of the complexity of the procedures this method does not seem particularly suitable for quick analysis and for``in ®eld'' determinations.…”
Section: Introductionmentioning
confidence: 99%
“…This would imply a mobile equilibrium (rapid dissociation and association), at least at low pH values. On the other hand, Wheelwright et al (7) estimated stability constants of rare earth-EDTA complexes polarographically by measuring the Cu displaced upon addition of rare earth to solutions equimolar in Cu and EDTA. Their values agreed with potentiometric estimates and indicated that uncomplexed Cu was accurately measured polarographically in the presence of CuEDTA complexes.…”
Section: Exchange Of Comments On Evaluation Of the Copper Anodic Stri...mentioning
confidence: 99%
“…Quantitative analysis with differential pulse polarography or voltammetry is usually done by measuring the differential current at its maximum and comparing this to a calibration curve (5)(6)(7). However, in several reports it has been demonstrated that small perturbations in the resistance of the electrochemical cell, or in the degree of electrochemical or chemical reversibility, can greatly affect both the differential current amplitude and its location on the applied potential axis (5, 6, [8][9][10].…”
mentioning
confidence: 99%